Effect of Shell Color and Nursery Depth on the Growth of Pearl Oyster Pinctada Maxima in Tekalok West Nusa Tenggara IndonesiaEffect of Shell Color and Nursery Depth on the Growth of Pearl Oyster Pinctada Maxima in Tekalok West Nusa Tenggara Indonesia - Syachruddin A R; Syukur Syukur; Septy Suryaningsih; Ratri Rahmawati; Asim L Khan (Indonesian Journal of Science and Technology, 2018)
The correlation between shell color and pearl oyster growth rates during the breeding phase is not well known and is then explored in this study. In addition, the effect of breeding depth on the growth is also assessed. The tests were conducted by monitoring the growth during a nursing season at a local company at Tekalok, East Lombok, Indonesia. The growth rates were measured from length extension, width extension and weight gain of a total of 4,493 seed samples over a three months nursing period. Results showed that average growth of each group of shell color was homogeneous with acceptable variance. The average length extension of all samples was 1.085 cm/month. The shell color significantly correlates with length extension, in which the yellow one being the highest elongation rate. However, no significant difference in width extension and weight gain was found at a specific condition. A slight decline in growth rate was shown at higher depth, but overall variations in growth rates are insignificant. Since the quality of the resulting pearls is better at higher depth, breeding should be done at higher depth, and further growth after nucleus inclusion can be done at lower depth to yield both optimum growth and high-quality pearl.